Functionalizing Thiosemicarbazones for Covalent Conjugation - Hohnsen, Johannes; Rryci, Lukas; Obretenova, Diana; Friedel, Joshua; Jouchaghani, Shahab; Klein, Axel (Molecules (Basel, Switzerland), 2024)
Thiosemicarbazones (TSCs) with their modular character (thiosemicarbazides + carbonyl compound) allow broad variation of up to four substituents on the main R1R2C=N(1)–NH–C(S)–N(4)R3R4 core and are thus interesting tools for the formation of conjugates or the functionalization of nanoparticles (NPs). In this work, di-2-pyridyl ketone was introduced for the coordination of metals and 9-anthraldehyde for luminescence as R1 and R2 to TSCs. R3 and R4 substituents were varied for the formation of conjugates. Amino acids were introduced at the N4 position to produce [R1R2TSC–spacer–amino acid] conjugates. Further, functions such as phosphonic acid (R–P(O)(OH)2), D-glucose, o-hydroquinone, OH, and thiol (SH) were introduced at the N4 position producing [R1R2TSC–spacer–anchor group] conjugates for direct NP anchoring. Phenyl, cyclohexyl, benzyl, ethyl and methyl were used as spacer units. Both phenyl phosphonic acid TSC derivatives were bound on TiO2 NPs as a first example of direct NP anchoring. [R1R2TSC–spacer–end group] conjugates including OH, S–Bn (Bn = benzyl), NH–Boc (Boc = tert-butyloxycarbonyl), COOtBu, C≡CH, or N3 end groups were synthesized for potential covalent binding to functional molecules or functionalized NPs through amide, ester, or triazole functions. The synthesis of the thiosemicarbazides H2NNH–C(S)–NR3R4 starting from amines, including amino acids, SCCl2 or CS2, and hydrazine and their condensation with dipyridyl ketone and anthraldehyde led to 34 new TSC derivatives. They were synthesized in up to six steps with overall yields ranging from 10 to 85% and were characterized by a combination of nuclear magnetic resonance spectroscopy and mass spectrometry. UV-vis absorption and photoluminescence spectroscopy allowed us to easily trace the dipyridyl imine and anthracene chromophores.